INFORMATION SYSTEM OF GOODS IN AND OUT USING FIFO METHOD - Zaenur Roziqin; Abdi Pandu Kusuma (Universitas Islam Balitar, 2021)
Information system in and out of inventory using the FIFO method is an information system to determine the inventory inventory in a company using the First In First Out method. FIFO itself is a sales method by selling incoming goods that are issued first to prevent a decline in the quality of goods due to expiration. FIFO inventory information systems have been widely used or developed in companies with various technologies and systems. The problem with EKO PS (Poultry Shop) Shop is that there is no information system available to manage inventory, so it cannot control the available inventory. Therefore, this study will analyze an information system in the form of a web-based FIFO inventory information system, so that inventory information can be known clearly and in detail and sales can be controlled using the FIFO method so that the FIFO inventory information system can be checked or viewed by admin as a user on the system.